Analisis Penerapan Keselamatan dan Kesehatan Kerja (K3) pada PT. Dayasa Ayasa Prima - Vivaldi Setyadi, Yogi; Baidlowi, Imam; Verlandes, Yuliasnita (Lembaga Pengembangan Kinerja Dosen, 2024)
This study is a qualitative study that aims to analyze the Implementation of Occupational Safety and Health (K3) at PT Dayasa Ayasa Prima. The Data Collection Technique in this Study was Conducted by Interview Method with Subject Employees from PT Dayasa Ayasa Prima. There are Three Aspects That Are the Focus (Scope) in This Study, Including K3 Training, PPE Facilities in the company, K3 guarantees and facilities for employees, and K3 Implementation. The results of this study include: 1. PT Dayasa Ayasa Prima has provided relevant training to employees to understand the importance of occupational safety and health, 2. PT Dayasa Ayasa Prima has complied with legal regulations and principles that require employees to use appropriate personal protective equipment, 3. PT Dayasa Ayasa Prima has implemented social security for employee welfare, including old age security, work accident insurance, death insurance, and health care insurance, and 4. PT Dayasa Ayasa Prima has also implemented an occupational health program that includes regular medical examinations for employees.